The relationships between motivational factors in learning and academic achievement among part-time adult learners in Kota Kinabalu - Lee, Pei Ling (2012)
This study provides an overview of the motivational factors of adults to pursue learning in higher education. The relationships between motivational factors of participation and academic achievement of adult learners in their learning are determined. Effort is also taken to find out the predictors for academic achievement of adult learners. This is a descriptive-correlational study using questionnaire as the mode of data collection. Five hundred and five respondents comprised of 255 adult learners in a conventional learning mode and 250 adult learners in a hybrid learning mode in Kota Kinabalu, Sabah were selected as samples of study. A thirty-item questionnaire, adapted from Boshier's EPS (1991) and Neill's TUSMSQ2 (2004), was used to measure the five motivational factors, which are personal development, career advancement, social pressure, social and communication improvement, and escapism. The findings indicate that personal development and career advancement are the prevalent motivational factors of participation in learning among adult learners. It is found that there Is a positive but low relationship between personal development and academic achievement among adult learners, while social pressure and escapism indicate negative and very low relationships with their academic achievement. In contrast, social and communication improvement, and career advancement do not correlate with academic achievement. Moreover, regression analysis reveals that personal development and social pressure are the predictors for academic achievement in adult education. Lastly, some recommendations and proposals for future studies are discussed.